Assessment of parental benzo[a]pyrene exposure-induced cross-generational neurotoxicity and changes in offspring sperm DNA methylome in medaka fish. Issue 1 (27th May 2022) - Wan, Teng; Au, Doris Wai-Ting; Mo, Jiezhang; Chen, Lianguo; Cheung, Kwok-Ming; Kong, Richard Yuen-Chong; Seemann, Frauke
Abstract: Previous studies have revealed that DNA methylation changes could serve as potential genomic markers for environmental benzo[a]pyrene (BaP) exposure and intergenerational inheritance of various physiological impairments (e.g. obesity and reproductive pathologies). As a typical aromatic hydrocarbon pollutant, direct BaP exposure has been shown to induce neurotoxicity. To unravel the inheritance mechanisms of the BaP-induced bone phenotype in freshwater medaka, we conducted whole-genome bisulfite sequencing of F1 sperm and identified 776 differentially methylated genes (DMGs). Ingenuity pathway analysis revealed that DMGs were significantly enriched in pathways associated with neuronal development and function. Therefore, it was hypothesized that parental BaP exposure (1 μg/l, 21 days) causes offspring neurotoxicity. Furthermore, the possibility for sperm methylation as an indicator for a neurotoxic phenotype was investigated. The F0 adult brains and F1 larvae were analyzed for BaP-induced direct and inherited toxicity. Acetylcholinesterase activity was significantly reduced in the larvae, together with decreased swimming velocity. Molecular analysis revealed that the marker genes associated with neuron development and growth ( alpha1-tubulin, mbp, syn2a, shh, and gap43 ) as well as brain development ( dlx2, otx2, and krox-20 ) were universally downregulated in the F1 larvae (3 days post-hatching). While parental BaP exposure at an environmentally relevant concentration could induce neurotoxicity in the developing larvae, the brain function of the exposed F0 adults was unaffected. This indicates that developmental neurotoxicity in larvae may result from impaired neuronal development and differentiation, causing delayed brain growth. The present study demonstrates that the possible adverse health effects of BaP in the environment are more extensive than currently understood. Thus, the possibility of multigenerational BaP toxicity should be included in environmental risk assessments.